Modelagem e simulação de uma célula a combustível alcalina a glicerol direto - Castro, Ubiranilson João de (2021)
A wide range of work has been carried out with the aim of improving the operation of fuel cells and making them applicable in different situations, in which mathematical modeling and computer simulation are great allies. In the present work, a comprehensive multidimensional model for simulating direct glycerol fuel cell (DGFC) was developed, a promising technology that still requires evolution in its study by computational technique. The model developed in the scope of computational fluid dynamics corresponds to a complete cell fed by glycerol, including parallel flow channels, diffuser layers, catalytic regions and anion exchange membrane. The implementation took place in commercial software, ANSYS / FLUENT, using the ability to customize equations via UDFs (User Defined Functions). Available experimental data of current density versus cell potential were used to adjust the parameters of the ideal model and realistic model of glycerol oxidation at the anode. With this, it is possible to implement anodic reaction kinetics in the global computational model as mass flow UDFs and, with the simulations, obtain details of internal processes such as speed field, fraction of the species involved and their distribution throughout the cell. It appears that there are significant variations in flow velocity and mass fractions of the species inside the device, which may result in a distribution of inhomogeneous current density.